Discovery of ROCK2 inhibitors through computational screening of ZINC database: Integrating pharmacophore modeling, molecular docking, and MD simulations. - Abdullah R Alanzi; Abdelaaty A Shahat; Bayan Abdullah Alhaidhal; Raghad Mohammad Aloatibi (PLoS ONE)
Rho-associated protein kinase 2 (ROCK2) is a serine/threonine kinase that is crucial for regulating various physiological processes and is part of the Rho-associated coiled-coil kinase family. The dysregulation of ROCK2 has been associated with a range of diseases, making it a promising target for therapy. In this study, a chemical feature-based pharmacophore model was developed on the co-crystal ligand (5YS) of ROCK2 to conduct the virtual screening of ZINC database, resulting in 4809 hits that were further subjected to molecular docking to find the binding affinities with ROCK2 protein. The binding affinities of the hits were analyzed and compounds in the range of -11.55 to -9.91 kcal/mol were selected for further analysis. The ADMET analysis identified two promising compounds, whose binding stability with the ROCK2 protein was further evaluated using molecular dynamics (MD) simulations. Simulation results revealed that the selected compounds remained closely bound to protein indicating that they can act as lead compounds to control the biological activity of ROCK2. However, further in vitro investigation is required to test the biological efficacy of the reported compounds.